Evaluating the association of interleukin-10 gene promoter -592 A/C polymorphism with lupus nephritis susceptibility - Emad Abdallah; Emam Waked; Mahmoud A. Abdelwahab (The Korean Society of Nephrology, 2016)
Background: Interleukin-10 (IL-10) is an important immunoregulatory cytokine. There are few studies evaluating the association between IL-10 and lupus nephritis (LN). The aim of this study was to evaluate the association of IL-10 gene promoter -592 A/C with LN susceptibility. Methods: The study was conducted on 84 patients with systemic lupus erythematosus (SLE). Patients were divided into LN group (Group I, 48 patients) and non-LN group (Group II, 36 patients). The -592 A/C polymorphisms in IL-10 promoter gene were determined by polymerase chain reaction and restriction fragment length polymorphism in both groups. IL-10 was determined by enzyme-linked immunosorbent assay. Frequencies of the genotypes were compared between LN and non-LN patients and among LN patients with different pathologic classes. Results: There was a significant increase in serum level of IL-10 (P = 0.001) in Group I compared with Group II and significant positive correlation between serum IL-10 and SLE disease activity index (r = 0.466, P = 0.001) in Group I. There were no significant differences in the distribution of the IL-10 gene promoter -592 A/C genotypes or the allele frequencies between Groups I and II. There was no significant difference between AC/CC and AA genotypes with SLE disease activity index, proteinuria, hematuria, anti-double-stranded DNA, and IL-10 in Group I. There was no significant difference in the distribution of AC and CC genotypes among different pathologic LN classes. Conclusion: IL-10 suggested to play a role in pathogenesis and development of LN. However, the promoter -592 A/C of IL-10 gene suggested to be not associated with serum IL-10 levels or LN susceptibility. In addition, it appears that promoter -592 A/C of IL-10 gene not associated with LN activity or the pathologic classes of LN.